Predictors of Dropout From Residential Treatment for Posttraumatic Stress Disorder Among Military Veterans - Smith, Noelle B.; Sippel, Lauren M.; Rozek, David C.; Hoff, Rani A.; Harpaz-Rotem, Ilan (Frontiers in Psychology, 2019)
BACKGROUND: Successful psychotherapy for posttraumatic stress disorder (PTSD) necessitates initial and sustained engagement. However, treatment dropout is common, with rates of 50-70% depending on the setting, type of treatment and how dropout is calculated. Dropout from residential treatment is less understood and could be impacted by participation of more symptomatic patient populations and reduced day-to-day barriers to engagement. Gaining insight into predictors of treatment dropout is critical given that individuals with greater symptoms are the most in need of successful treatments but also at higher risk of unsuccessful psychotherapy episodes. AIM: The aim of the current study was to examine predictors of treatment dropout among veterans receiving residential treatment for PTSD. METHOD: The study included 3,965 veterans who initiated residential PTSD treatment within a Department of Veterans Affairs program during Fiscal Year 2015 and completed self-report measures of demographics and psychiatric symptoms at admission. RESULTS: In our sample (N=3,965, 86.5% male, mean age = 45.5), 27.5% did not complete the residential program (n = 1,091). Controlling for age, marital status, combat/non-combat trauma, and facility, generalized estimating equation modeling analysis indicated greater PTSD symptoms and physical functioning at admission were associated with reduced likelihood of completing the residential program. There were significant differences in trauma-focused psychotherapy received by individuals who dropped out of residential treatment and those who did not. Among veterans who dropped out, 43.6% did not get any trauma-focused psychotherapy; 22.3% got some, but less than 8 sessions; and 34.1% got at least 8 sessions; compared to 37.3%, 4.8%, and 57.9%, respectively, among program completers. CONCLUSIONS: Dropout rates from residential PTSD programs indicate that at least one in four veterans do not complete residential treatment, with more symptomatic individuals and those who do not receive trauma-focused therapy being less likely to complete.